PERAMALAN DINAMIS PRODUKSI PADI DI JAWA TENGAH MENGGUNAKAN METODE KOYCK DAN ALMON - Firdha Rahmatika Pratami; Sudarno Sudarno; Dwi Ispriyanti (Jurnal Gaussian, 2016)
Paddy is one of the staple crops that have strategic value and has a great influence in economic, environmental, social and political. Almost of Indonesia's population consumes rice every day. Because of that, need models to determine or predict the amount of paddy production in Central Java for the future. Because the data used is the historical data, there will be a regression analysis that takes into account the time. If the regression model include not only the value of the independent variable X at this time, but also the value of the past (lagged), this model  called a distributed-lag model. The methods used in determining the equation of distributed-lag are Koyck and Almon method. Koyck method used to determine the estimated dynamic model of distributed-lag time difference (lag) is unknown. Almon method used to determine the estimated dynamic model of distributed-lag time difference (lag) is known. Selection of the best model is using Mean Absolut Percentage Error criteria. According the result of the analysis, using Almon model has better result than Koyck Model.Keyword: Paddy, Distributed-lag model, Koyck, Almon